Islamic Service Quality and Patient Loyalty: Investigating the Role of Satisfaction in Healthcare Contexts - Widiastuti, Widiastuti; Indartono, Setyabudi; Sa'adah, Nurus (Society, 2024)
This study examines the mediating role of patient satisfaction in the relationship between Islamic service quality and patient loyalty at the General Hospital of Welfare Development Unit Muhammadiyah Bantul (Rumah Sakit Umum Pembina Kesejahteraan Umat Muhammadiyah Bantul), addressing concerns over declining patient visits. Using a survey of 150 respondents and Partial Least Squares-Structural Equation Modeling (PLS-SEM), the results indicate that tangible dimensions of Islamic service quality do not significantly affect satisfaction or loyalty. However, reliability, responsiveness, assurance, and empathy positively and significantly influence both outcomes. Patient satisfaction does not mediate these effects, suggesting that patients directly value the integration of Islamic principles in service delivery. These findings emphasize the critical role of culturally aligned healthcare services in building trust and loyalty, offering insights for policymakers and healthcare practitioners to develop inclusive and patient-centered service strategies aligned with societal and religious values.